3 - Feminist Scholarship, Femocracy and the Glass Ceiling in Zimbabwean Politics - Chadambuka, Patience (Journal of Higher Education in Africa, 2022)
This article analyses the contributions of feminist scholarship in enhancing women’s political participation in Zimbabwe. After years of critical and feminist theory and quota systems it is noted that women’s participation in politics has achieved insignificant contributions towards the attainment of gender equality. The article uses the glass ceiling concept to argue that the presidium marks women’s glass ceiling in Zimbabwean politics. Zimbabwe is yet to acknowledge and accept that women are presidential material. It is further argued that female politicians have embraced their ascendancy to the country’s higher political offices as an end in itself and not as a means to uplift women’s lives. Using Crenshaw’s concept of intersectionality, the article also brings to light how female politicians seem to be engendering agendas that have nothing to do with women as they are used as objects to further patriarchal power struggles. It is thus recommended that there is a need to create synergy between feminists and female politicians in order to earnestly represent the needs of women once they get into political office. It is argued, however, that this transformation should begin with educational institutions which are still male-dominated. The idea is that universities and political offices need to prioritise gender equality so that Africa’s social transformation that uplifts the lives of women may be achieved.